Benefits of massive weight loss on symptoms, systemic inflammation and cartilage turnover in obese patients with knee osteoarthritis. Issue 1 (26th October 2010) - Richette, Pascal; Poitou, Christine; Garnero, Patrick; Vicaut, Eric; Bouillot, Jean-Luc; Lacorte, Jean-Marc; Basdevant, Arnaud; Clément, Karine; Bardin, Thomas; Chevalier, Xavier
Abstract : Objective: To investigate the effect of massive weight loss on (1) knee pain and disability, (2) low-grade inflammation and metabolic status and (3) joint biomarkers in obese patients with knee osteoarthritis (OA). Methods: 140 patients involved in a gastric surgery programme were screened for painful knee OA, and 44 were included (age 44 ± 10.3 years, body mass index (BMI) 50.7 ± 7.2 kg/m 2 ). Clinical data and biological samples were collected before and 6 months after surgery. Results: Before surgery, interleukin 6 (IL-6) levels were correlated with levels of high-sensitivity C reactive protein (hsCRP) (p=0.006) and Helix-II (p=0.01), a biomarker of cartilage turnover, and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) function score (p=0.03). Surgery resulted in substantial decrease in BMI (−20%). Levels of insulin and insulin resistance were decreased at 6 months. Knee pain decreased after surgery (24.5 ± 21 mm vs 50 ± 26.6 mm; p<0.001), and scores on all WOMAC subscales were improved. Levels of IL-6 (p<0.0001), hsCRP (p<0.0001), orosomucoid (p<0.0001) and fibrinogen (p=0.04) were decreased after surgery. Weight loss resulted in a significant increase in N-terminal propeptide of type IIA collagen levels (+32%; p=0.002), a biomarker of cartilage synthesis, and a significant decrease in cartilage oligomeric matrix protein (COMP) (−36%; p<0.001), a biomarker of cartilage degradation. Changes in COMP concentration were correlated with changes in insulin levels (p=0.02) and insulin resistance (p=0.05). Conclusion: Massive weight loss improves pain and function and decreases low-grade inflammation. Change in levels of joint biomarkers with weight loss suggests a structural effect on cartilage.